An Analysis of Learning Strategies in English Speaking Skills Among Second Year Students at English Department UNP - Ikhlaulia, Wanda; Solusia, Carbiriena (Universitas Negeri Padang, 2024)
Speaking plays a crucial role in the learning process, serving as a vital channel for effective interaction. The importance of speaking in learning is emphasized by recognizing language learning strategies (LLS) as valuable tools for enhancing proficiency in a foreign language. This research aims to analyze the learning strategies employed by second-year students in their speaking classes within the English department at UNP, majoring in English education. The study focuses on English education students enrolled in 2022, with a total population of 241 students from 10 classes. Using simple random sampling, 5 students from each class were selected as the sample, resulting in a total of 50 participants. A questionnaire, encompassing six aspects of language learning strategies (cognitive, metacognitive, memory, compensatory, affective, and social) adapted from Oxford's (1990) framework, was distributed to students in speaking classes. The questionnaires were administered online through Google Forms. The data analysis revealed that the strategy students most commonly employed in their speaking classes pertained to the cognitive aspect of language learning. The ranking of the aspects, from the first to the sixth, was cognitive, social, memory, metacognitive, compensatory, and affective.